Production and Safety of Closed House Waste as A Source of Protein For Non Ruminan Rations - I N.T. Ariana; I G.N.G. Bidura; D.A. Warmadewi; B.R.T. Putri; I N.S. Miwada; Bulkaini Bulkaini (Jurnal Biologi Tropis, 2022)
Closed house waste which has so far been considered a contributor to environmental pollution if processed professionally, can be reused as a component of non-ruminant rations. The purpose of this study is to determine the production (potential, quantity, and quality) of broiler farm waste that is maintained in a closed house system. The cost of production of non-ruminant livestock (pig) 70-80% is still occupied by the cost of feed. The price of commercial concentrate is relatively expensive, which is a reason to look for alternative feed sources. The discovery of potential closed house chicken farm waste and innovative products as a source of protein in rations for non-ruminant (pig-poultry) is expected to the feed problem. Innovative product protein concentrate chicken farm waste of closed house (WCH) system that is cheap and competitive is produced through three stages of research: identify the type and availability of waste, its nutrient content, formulate various protein concentrate formulas, and small-scale tests on pigs with metabolic cage to determine metabolized energy content and digestibility. The results showed that the type of closed house waste (WCH) that has the potential as alternative animal feed is the waste of dead-refused chickens, and litter mixed with scattered feed. Production data in 4 periods of rearing, obtained the number of dead and rejected chickens weighing 850.7 kg (212.7 kg/period), and litter weight of 4000 kg (1000kg/period). Nutrient content of flour mixed with closed house waste (WCH), protein: 36.58%, crude fat: 4.42%, gross energy Kcal/gram. aboratory test of WCH was negative for Eschericia colli and Salmonella shigella, Coliform < 3.0 CFU/g, mold 200 CFU/g. The conclusion of this study is that the waste from closed house (LCH) broiler farms has the potential as a source of protein in alternative feeds for rumonants (chicken and pig).